BATIK GEDHOG DESA KEDUNGREJO-TUBAN SEBAGAI SUMBER BELAJAR BERBASIS ETNOPEDAGOGI DI SEKOLAH DASAR - NUFITA SARI, RINA; GUNANSYAH, GANES (Jurnal Penelitian Pendidikan Guru Sekolah Dasar, 2018)
Ethnopedagogy is education that learns about the culture in which it covers various field. The purpose of this study was to find out the material content in batik gedhog as a source of ethnopedagogical based learning in primary schools and to know how to integrate the content of ethnopedagogical material and in integrated learning in the primary school in accordance with 21st century learning. This research uses qualitative research with ethnography method. The data collection techniques is participative observation, indepth interviews, and document review. The results of this study indicate that batik gedhog contains several aspects such as Mathematics, Social Studies, Science, Religion, Indonesian Language, and Civic Education. The finding of the material are then integrated into learning that can be applied in primary school based on existing basic competencies and can be developed into several models of learning appropriate Curriculum 2013 is Webbed and Connected. Keywords: ethnopedagogy, batik gedhog, learning resources